The Estimation of Total Lengths in the Earlier Ages of Mirror Carp (Cyprinus carpio L., 1758) Using Back-Calculation Methods - Teksar, Can Kaan; Calta, Metin (My University, 2020)
In this study, the total lengths of the smaller mirror carp, that could not be caught, were estimated with the back-calculation methods using the scale and otolith lengths of larger fish. For this purpose, 50 fish samples were captured from Keban Dam Lake during October-November 2017 and October-December 2018. They were 4-9 in ages, 31.2-47.2 cm in total length and 442.5-1497.8 g in weight. The age of fish and the lengths of each age ring on scale and otolith were determined by using LAS V4.8 image analysis program attached to Leica S8APO microscope. The total lengths of fishes were calculated using Fraser-Lee and Dahl-Lea back-calculation equations for scale and otolith respectively. The mean total lengths calculated for all age groups from scale radius lengths and otolith lengths were L1:16.1, L2:21.3, L3:27.3, L4:30.5, L5:35.7, L6:36.7, L7:42.9, L8:45.3 ve L9: 45.9 cm and L1:14.2, L2:17.8, L3:22.8, L4:25.5, L5:33.1, L6:36.0, L7:41.0, L8:41.4 ve L9:44.0 cm respectively. In all age groups, total lengths of fish calculated from otolith lengths were found lower than total lengths of fish calculated from scale lengths.
Keywords: Cyprinus carpio; scale; otolith; Mirror carp; back calculation; fish length